Sosialisasi Digital Marketing Terhadap Usaha Mikro Kecil dan Menengah di Dusun Kradenan - Subagio, Azka Raisa (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The rapid development of information technology has transformed marketing strategies from conventional to digital approaches. Digital marketing enables businesses, including Micro, Small, and Medium Enterprises (MSMEs), to reach broader markets, increase competitiveness, and enhance customer engagement. However, in Dusun Kradenan, many MSME actors still rely on traditional marketing methods due to limited digital literacy and technological resources. Objective: This study aims to enhance the understanding and skills of MSME actors in Dusun Kradenan in utilizing digital marketing for business promotion. Additionally, it seeks to analyze the impact of digital marketing socialization conducted by community service students on local business competitiveness. Method: The method used in this socialization was a participatory approach, involving direct interaction between students and MSME actors. The activities included an initial survey to identify business needs, preparation of digital marketing materials, workshop implementation, evaluation, and post-socialization mentoring to ensure sustainable digital marketing adoption. Result: The socialization was attended by 15 MSME actors in the food and beverage sector. The results showed that 80% of participants felt more confident in using social media for product promotion. Additionally, there was a significant increase in MSMEs adopting digital platforms such as Instagram and Facebook for marketing. A notable case study was Carade Cake and Cookies, which experienced a 60% increase in sales within two months after implementing digital marketing strategies. However, some MSME actors still faced challenges related to technical skills and resource limitations. Conclusion: The digital marketing socialization positively impacted MSME actors in Dusun Kradenan by improving their digital marketing knowledge and business competitiveness. Although challenges remain, continuous mentoring is crucial to ensuring the sustainability of digital marketing adoption in the community.